Theoria to Theory (and Back Again): Integrating Masterman's Writings on Language and Religion - Wiseman, Harris (Zygon, 2022)
This article explores three aspects of Masterman's language work and applies them to questions of spiritual intelligence: metaphor, coherence, and ambiguity. First, metaphor, which is ubiquitous in ordinary language, both leads and misleads in religious and scientific understanding. Masterman's case for a “dual-approach” to thinking, both speculative and critical, is explored and tied to concepts of moral-spiritual development per Pierre Hadot and Hannah Arendt. Second, Masterman's work on machine translation presents semantic disambiguation as an emerging coherence wherein one gradually hones in on meaning through features of ordinary language (like redundancy and repetition). This is applied to the problem of comprehending difficult spiritual language, and tied to spiritual stretching and spiritual cartography. Third, Masterman's work with thesauri, rather than relying on words as having fixed meanings, appeals to a concept of semantic spaces, nebulae of variously interconnected meanings. This is constructed into an exhortation to reambiguate overfamiliar religious language, to reinvest one's quotidian surroundings with spiritual meaning through defamilarization.